Prognostic nutritional index negative associated with mortality in older Japanese patients with dysphagia - Pei, Ruijun; Wang, Donghao (Frontiers in Nutrition, 2025)
BackgroundThe prognostic nutritional index (PNI) has been proven to represent a biomarker for predicting prognosis in many groups of patients with severe diseases. However, few studies have investigated the association between PNI and mortality in Japan older people with dysphagia patients.ObjectiveThis retrospective cohort study aimed to assess the prognostic value of PNI in older Japanese patients with dysphagia.MethodsWe analyzed data from 248 patients diagnosed with dysphagia at a single center between January 2014 and January 2017. According to PNI score, all patients were divided into normal nutrition group (PNI ≥ 38), moderate malnutrition group (35 ≤ PNI < 38) and severe malnutrition group (PNI < 35). Cox regression analysis was used to compare the mortality rates among the three groups. Subgroup analyses were conducted, and Kaplan-Meier curves were used to determine the median survival times.ResultsThe mean age of the patients was 83.0 ± 9.3 years, with a male-to-female ratio of 0.64:1. Of the patients, 180 received percutaneous endoscopic gastrostomy (PEG) and 68 received total parenteral nutrition (TPN). After adjusting for all covariates, the multivariable Cox regression analysis revealed a significant association between PNI and the risk of mortality (HR = 0.94, 95% CI: 0.92–0.97, P < 0.001). Compared with the normal nutrition group, the mortality rate of severe malnutrition group was significantly higher (P = 0.007). The adjusted hazard ratios for the severe and moderate malnutrition groups were 1.83 (95%CI: 1.18–2.84, P = 0.007) and 1.39 (95%CI: 0.81–2.4, P = 0.234), respectively. Kaplan-Meier curves indicated median survival times of 189, 447, and 864 days for severe malnutrition group, moderate malnutrition group, and normal nutrition group, respectively.ConclusionPNI was negatively associated with mortality in older Japanese patients with dysphagia. There was no interaction for the subgroup analysis. The result was stable.